COVID-19 During Development: A Matter of Concern - Saavedra, Lucas Paulo Jacinto; Prates, Kelly Valério; Gonçalves, Gessica Dutra; Piovan, Silvano; Matafome, Paulo; Mathias, Paulo Cezar de Freitas (Frontiers in Cell and Developmental Biology, 2021)
A new infectious disease, COVID-19 has spread out around the world. The most common symptoms of SARS-CoV-2 infection are cough and fever, but severe cases can develop acute respiratory distress syndrome. The main receptor for SARS-CoV-2 in human tissue is angiotensin-converting enzyme 2 (ACE2), being lungs, heart and kidneys the most affected organs. Besides the inflammatory process and tissue damage, the presence of a cytokine “storm” has been related to higher mortality rate. Other infectious viral diseases, such as Zika, chikungunya and influenza were associated with complications in pregnant women, such as growth restriction, malformation, preterm birth, low birth weight, miscarriage and death, although they can also cause developmental disorders in infants and adolescents. Evidence points out that stressors during pregnancy and infancy may lead to the development of obesity, diabetes and cardiovascular disease. Therefore, we hypothesize that COVID-19 infection during the critical phases of development can program the individual to chronic diseases in adulthood. It is important that COVID-19 patients have a proper monitoring, as a way to avoid expensive costs to public health in the future.